Health systems resilience in fragile and shock-prone settings through the prism of gender equity and justice: implications for research, policy and practice - Wesam Mansour; Abriti Arjyal; Chad Hughes; Emma Tiange Gbaoh; Fouad Mohamed Fouad; Haja Wurie; Hnin Kalayar Kyaw; Julie Tartaggia; Kate Hawkins; Kyu Kyu Than; Lansana Hassim Kallon; Maya Abou Saad; et al. (Conflict and Health, 2022)
Abstract Fragile and shock-prone settings (FASP) present a critical development challenge, eroding efforts to build healthy, sustainable and equitable societies. Power relations and inequities experienced by people because of social markers, e.g., gender, age, education, ethnicity, and race, intersect leading to poverty and associated health challenges. Concurrent to the growing body of literature exploring the impact of these intersecting axes of inequity in FASP settings, there is a need to identify actions promoting gender, equity, and justice (GEJ). Gender norms that emphasise toxic masculinity, patriarchy, societal control over women and lack of justice are unfortunately common throughout the world and are exacerbated in FASP settings. It is critical that health policies in FASP settings consider GEJ and include strategies that promote progressive changes in power relationships. ReBUILD for Resilience (ReBUILD) focuses on health systems resilience in FASP settings and is underpinned by a conceptual framework that is grounded in a broader view of health systems as complex adaptive systems. The framework identifies links between different capacities and enables identification of feedback loops which can drive or inhibit the emergence and implementation of resilient approaches. We applied the framework to four different country case studies (Lebanon, Myanmar, Nepal and Sierra Leone) to illustrate how it can be inclusive of GEJ concerns, to inform future research and support context responsive recommendations to build equitable and inclusive health systems in FASP settings.